FOREIGN POLICY: THEORETICAL APPROACHES - Ruzimurodov, Jasur; Turayev, Abror (Журнал истории и общества, 2021)
This article discusses the concept of foreign policy and its interpretations, theoretical approaches. Theories explaining foreign policy are compared, and approaches to the analysis of key factors behind foreign policy are considered.